2018
DOI: 10.35188/unu-wider/2018/631-9
|View full text |Cite
|
Sign up to set email alerts
|

Inequality trends and dynamics in India: The bird’s-eye and the granular perspectives

Abstract: This study has been prepared within the UNU-WIDER project on 'Inequality in the giants'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…From a socio-politico-cultural point of view, the studies reviewed suggest that some of the intentional burn injuries are connected to the practice of dowry payments. This practice has been legally prohibited in countries such as Nepal, Pakistan, Sri Lanka and, since 1961, India (Banerjee, 2014; Ministry of Women & Child Development, 2020), but the law is not strongly enforced in many communities due to socio-cultural expectations (Dang et al, 2018). Interestingly, dowry payments remain legal in the United Kingdom (Women’s UN Report Network, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…From a socio-politico-cultural point of view, the studies reviewed suggest that some of the intentional burn injuries are connected to the practice of dowry payments. This practice has been legally prohibited in countries such as Nepal, Pakistan, Sri Lanka and, since 1961, India (Banerjee, 2014; Ministry of Women & Child Development, 2020), but the law is not strongly enforced in many communities due to socio-cultural expectations (Dang et al, 2018). Interestingly, dowry payments remain legal in the United Kingdom (Women’s UN Report Network, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The dip in these cases may have resulted from the 2010 judgment requiring prior harassment of the victim associated with a dowry shortfall which made it harder to register a dowry death but presumably also harder to prove beyond a reasonable doubt that it was a dowry death, and not in fact. [48] Furthermore, qualitative research has shown that the families of dowry death cases deter from accusing the husband or his family due to fear of issues with upbringing of the children of their daughter [47]. Also dowry deaths or related suicide deaths are less likely to be reported by the natal family, who fear social stigma and negative impact on marriages of their other daughters [42,49].…”
Section: Dowry Deathsmentioning
confidence: 99%